Mindful parenting, parenting self-efficacy, and marital satisfaction of mother with toddler on family resilience during pandemic - Sri Redatin Retno Pudjiati; Khusnul Khatimah; Tiffany Lisa Marsaulina; Firyal Fahirah Fadilah; Aulya Diesa Maretha (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
The COVID-19 pandemic has both positive and negative impacts on individuals in affected areas. For mothers who have many roles at home, this impact can cause stress due to sudden changes in the family. Therefore, it is important to know whether mindful parenting, parenting self-efficacy, and marital satisfaction are important factors for family resilience. This study used a quantitative approach to examine the roles of those factors. Data obtained using Walsh Family Resilience Questionnaire, Interpersonal Mindful Parenting, Self-Efficacy Parenting Task Index-Toddler Scale Short Form and ENRICH Marital Satisfaction (EMS) Scale were analyzed by multiple regression. Based on data from 116 mothers who have toddlers (Mage = 28.46, SD = 3.14), it is known that the associations of mindful parenting, parenting self-efficacy, and marital satisfaction predict 50% of family resilience positively. Furthermore, marital satisfaction provides the largest significant unique contribution, followed by a smaller contribution by parenting self-efficacy, while mindful parenting did not. This shows that internal and external factors by the mother both contribute to creating a resilient family during the Covid-19 Pandemic, thus, it is essentially important to ensure that mothers receive good support from their partners and are confident in providing positive care for their children.